A field study of the use of methoprene for West Nile virus mosquito control. Issue 6 (1st November 2006) - Des Lauriers, Angelune; Gris, Greg; Baker, Stacey L; Sze, Kevin; Chan, Jack; Li, James
Abstract : The occurrence of vector-borne West Nile virus in Canada has resulted in the use of larvicides for widespread urban mosquito control. To determine the fate of larvicides in storm drainage systems, three catch basins in Toronto, Ontario were treated with methoprene (Altosid) pellets three times over the summer of 2003, at the recommended mosquito control dose of 0.7 g per catch basin. Daily monitoring included: methoprene concentration analysis, precipitation in the area, the presence of mosquito larvae, and the chemical composition of catch basin sumps. A model catch basin in the laboratory was also dosed with methoprene pellets and sampled daily to observe concentration over time under quiescent conditions. It was found that (1) the methoprene concentration at the catch basins fell below the minimum lethal concentration after one or two weeks after treatment; (2) rainfall flushed methoprene from the catch basins to the storm sewer outfall at concentrations lower than the level that may cause ecosystem damage; and (3) the methoprene concentrations in the experiments exhibited a double peak decay pattern.